2021
DOI: 10.3389/fped.2021.753226
|View full text |Cite
|
Sign up to set email alerts
|

ATLAS2030 Pediatric Gait Exoskeleton: Changes on Range of Motion, Strength and Spasticity in Children With Cerebral Palsy. A Case Series Study

Abstract: Background: Cerebral Palsy (CP), the most common motor disability in childhood, affects individual's motor skills, movement and posture. This results in limited activity and a low social participation. The ATLAS2030 exoskeleton is a pediatric device that enables gait rehabilitation for children with neurological or neuromuscular pathologies with gait pathology.Purpose: To study changes in relation to range of motion (ROM), strength and spasticity in children with CP after using the ATLAS2030 gait exoskeleton.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
2
7
0
1
Order By: Relevance
“…Other studies have evaluated changes in maximal isometric strength exerted in children diagnosed with cerebral palsy. Bayón et al [26] with CPWalker (CSIC, Spain) and Delgado et al [17] with ATLAS2030 (Marsi Bionics, Spain) found improvements in strength after 8 weeks and 4 weeks of training with a walking exoskeleton, mainly showed important peaks of improvement for hip and knee flexion-extension, in line with our study. However, Kuroda et al [27] with HAL ® (Cyberdine, Japan) reported a decrease in knee extensors strength during 4-week training.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other studies have evaluated changes in maximal isometric strength exerted in children diagnosed with cerebral palsy. Bayón et al [26] with CPWalker (CSIC, Spain) and Delgado et al [17] with ATLAS2030 (Marsi Bionics, Spain) found improvements in strength after 8 weeks and 4 weeks of training with a walking exoskeleton, mainly showed important peaks of improvement for hip and knee flexion-extension, in line with our study. However, Kuroda et al [27] with HAL ® (Cyberdine, Japan) reported a decrease in knee extensors strength during 4-week training.…”
Section: Discussionsupporting
confidence: 91%
“…The main differences between the ATLAS 2030 and its research prototype are in software upgrades, exoskeleton torso structure, battery and orthotics. In addition, ATLAS 2030 has been tested in children with cerebral palsy obtaining good results in ROM, strength and spasticity after the use of the exoskeleton [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bayon et al [30] designed an exoskeleton for CP children with 6 active DOFs at the hip, knee, and ankle, although requiring a smart walker to ensure balance. Similar designs with extra walker are also proposed for CP or SMA 2 children [31], [32]. However, the walker limited the mobility and the patient only follows a fixed gait pattern where the capability of maintaining balance is not trained.…”
Section: Introductionmentioning
confidence: 99%
“…Bayon et al [30] designed an exoskeleton for CP children with 6 active DOFs at the hip, knee, and ankle, although requiring a smart walker to ensure balance. Similar designs with extra walker are also proposed for CP or SMA 2 children [31], [32]. However, the walker limited the mobility and the patient only follows a fixed gait pattern where the capability of maintaining balance is not trained.…”
Section: Introductionmentioning
confidence: 99%